GERAKAN LITERASI ISLAM DI KALANGAN GENERASI MUDA - Muhammad Taufiq (NIHAYAH: Journal of Islamic Studies, 2025)
The advancement of information technology and the transformation of digital culture have significantly influenced the religious behavior of young Muslims in Indonesia. Amid the massive and diverse flow of information, Islamic literacy has emerged as a strategic necessity to build an inclusive, contextual, and moderate understanding of Islam. This article aims to examine the dynamics of Islamic literacy movements among the younger generation from 2018 to 2025, using a descriptive qualitative approach based on library research. The findings show that Islamic literacy is no longer limited to the ability to read classical religious texts but has evolved into a cultural movement that integrates textual understanding, critical thinking, and the use of digital media as a space for religious expression. Various initiatives have emerged, including communities, podcasts, digital pesantren, and youth forums that actively produce and disseminate inclusive and reflective Islamic discourse. Islamic literacy plays a vital role in strengthening the religious identity of young Muslims, countering radicalism, and expanding interfaith dialogue. Future strategies to enhance this movement involve collaboration between academics, literacy activists, and Muslim influencers, as well as the optimal use of digital technology grounded in the values of maqāṣid al-sharī‘ah. Strengthening Islamic literacy equips the younger Muslim generation to become agents of change who uphold the values of Islam rahmatan lil-‘ālamīn in a pluralistic society and within the challenges of the digital era.